Draft Genome Sequence of Vibrio parahaemolyticus VH3, Isolated from an Aquaculture Environment in Greece - Castillo, Daniel (Genome Announc, 2015)
Vibrio parahaemolyticus is an important foodborne pathogen responsible for gastroenteritis outbreaks globally. It has also been identified as an important pathogen in aquatic organisms. Here, we report a draft genome sequence of V. parahaemolyticus, strain VH3, isolated from farmed juvenile greater amberjack, Seriola dumerili, in Greece.